2002
DOI: 10.1046/j.1365-2885.2002.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of enrofloxacin in intestinal tissue and contents of healthy pigs after oral and intramuscular administrations

Abstract: The concentration of enrofloxacin in plasma, intestinal tissue, lymph nodes and intestinal contents was investigated in healthy pigs after oral (p.o.) and intramuscular (i.m.) administration of a single dose of 2.5 mg/kg bw. Tissue and content samples were collected from jejunum, ileum, caecum and colon from pigs killed at 2, 3 and 6 h after dosing. Intramuscular administration resulted in significantly higher concentrations in plasma, intestinal tissue and lymph nodes at 2 h but not at 3 or 6 h compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 26 publications
6
44
2
Order By: Relevance
“…faeces and 54% in the urine [15][16][17]. A recent study clearly indicated that an individual administration for a food animal by the intra-muscular route seems to be preferable to the oral route to ensure an immediate high concentration and thereby avoid an initial selection for resistant mutants [18]. All these elements must be taken into account when using an adapted treatment.…”
Section: Discussionmentioning
confidence: 99%
“…faeces and 54% in the urine [15][16][17]. A recent study clearly indicated that an individual administration for a food animal by the intra-muscular route seems to be preferable to the oral route to ensure an immediate high concentration and thereby avoid an initial selection for resistant mutants [18]. All these elements must be taken into account when using an adapted treatment.…”
Section: Discussionmentioning
confidence: 99%
“…: Gram-positive and Gram-negative bacteria, mycoplasmas and chlamydia (Boothe et al 2006, Elmas et al 2006, Grobbel et al 2007). Owing to its lipophilic properties, enrofloxacin is rapidly absorbed from the alimentary tract, quickly reaches therapeutic concentration (De Lucas et al 2008, Bimazubute et al 2010) and easily penetrates into the tissues and cells (Anadon et al 1999, Wiuff et al 2002. In the body of different species of animals enrofloxacin is subjected to metabolic transformation into ciprofloxacin, which chemotherapeutic activity is comparable to the maternal substance (Riddle et al 2000, Grobbel et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to animal tissue and milk there are only few methods describing the analysis of fluoroquinolones in aquatic systems (Hirsch et al 1998;Golet et al 2001;Ternes et al 2001;Turiel et al 2003) soils (Golet et al 2002;Morales-Munoz et al 2004;Turiel et al 2006;Martinez-Carballo et al 2007) and animal feces (Wiuff et al 2002;Sunderland et al 2004). These analytical methods based on the accelerated solvent extraction, microwave or ultrasonic assisted extractions with a number of different aqueous, organic solvents or their combination.…”
Section: Introductionmentioning
confidence: 99%